Precipitation of thin-film organic single crystals by a novel crystal growth method using electrospray and ionic liquid film. (6th March 2018) - Ueda, Hiroyuki; Takeuchi, Keita; Kikuchi, Akihiko
Abstract: We report an organic single crystal growth technique, which uses a nonvolatile liquid thin film as a crystal growth field and supplies fine droplets containing solute from the surface of the liquid thin film uniformly and continuously by electrospray deposition. Here, we investigated the relationships between the solute concentration of the supplied solution and the morphology and size of precipitated crystals for four types of fluorescent organic low molecule material [tris(8-hydroxyquinoline)aluminum (Alq3 ), 2-(4-biphenylyl)-5-(4- tert -butylphenyl)-1, 3, 4-oxadiazole (PBD), N, N ′-bis(3-methylphenyl)- N, N ′-diphenylbenzidine (TPD), and N, N -bis(naphthalene-1-yl)- N, N -diphenyl-benzidine (NPB)] using an ionic liquid as the nonvolatile liquid. As the concentration of the supplied solution decreased, the morphology of precipitated crystals changed from dendritic or leaf shape to platelike one. At the solution concentration of 0.1 mg/ml, relatively large platelike single crystals with a diagonal length of over 100 µm were obtained for all types of material. In the experiment using ionic liquid and dioctyl sebacate as nonvolatile liquids, it was confirmed that there is a clear positive correlation between the maximum volume of the precipitated single crystal and the solubility of solute under the same solution supply conditions.